SOCIO-ECONOMIC BENEFITS OF OIL PALM PRODUCTION ON RURAL LIVELIHOOD: A CASE STUDY OF RURAL FARMERS IN KARONGA DISTRICT, MALAWI - Mweta, Noel; Somuah-Obeng, Alex; Windie Ansah, John (Journal of Agri Socio Economics and Business, 2024)
Oil palm (Elaeis guineensis) production has been essential in addressing socio-economic challenges, particularly in countries such as Indonesia, Malaysia, Honduras, Ghana, and Nigeria. For instance, oil palm production has provided food among the rural populations, creating job opportunities, generating income, hence offering potential pathway for reducing rural poverty. In Malawi, oil palm production is an old tradition practiced by the Nyakyusa people, residing in Karonga District. These people have been involved in producing crude palm oil and soap using indigenous technologies that have been handed down over decades from generation to generation. Despite these indigenes being involved in this agricultural activity, the exploration of how this activity impact their lives remain under researched. Using mixed method and sequential explanatory design, with data collected through questionnaire, in-depth interviews, and focus group discussion, the study examined the socio-economic benefits of oil palm production on rural livelihood, citing Karonga district as area of case study. The findings of the study revealed that through oil palm production, rural farmers perceive this agricultural activity as crucial in sustaining their livelihood as it provides cooking oil, creates once-off job opportunities and generate income, hence meeting basic needs. Also, though oil palm production sustains their livelihood, the study revealed problems such as availability of markets, hindering the progress of this agricultural activity. The study therefore recommends that to unlock the full potential of oil palm production, the government through the Malawi Ministry of Agriculture should help farmers to market their produce.